Miocene to Pleistocene osmium isotopic records of the Mediterranean sediments. (21st January 2016) - Kuroda, Junichiro; Jiménez‐Espejo, Francisco J.; Nozaki, Tatsuo; Gennari, Rocco; Lugli, Stefano; Manzi, Vinicio; Roveri, Marco; Flecker, Rachel; Sierro, Francisco J.; Yoshimura, Toshihiro; Suzuki, Katsuhiko; Ohkouchi, Naohiko
Abstract: In the late Miocene the Mediterranean Sea experienced a salinity crisis and thick sequences of evaporites precipitated across the deep and marginal basins. In this study we report Os isotopic records from Deep Sea Drilling Project and Ocean Drilling Project cores in the Mediterranean: the Balearic Sea (Site 372), the Tyrrhenian Sea (Site 654), the Ionian Basin (Site 374), and the Florence Rise (Sites 375–376), as well as Integrated Ocean Drilling Project Site U1387 in Gulf of Cadiz, North Atlantic. Pliocene‐Pleistocene sediments at all sites show 187 Os/ 188 Os values close to that of the coeval ocean water, indicating that the Mediterranean was connected to the North Atlantic. Evaporitic sediments deposited during the latest Miocene, however, have 187 Os/ 188 Os values significantly lower than coeval ocean water values. The offset of the Mediterranean evaporite 187 Os/ 188 Os is attributed to limited exchange with the North Atlantic during the Messinian salinity crisis. The source of unradiogenic Os is likely to be weathering of ultramafic rocks (ophiolites) cropping out in the Mediterranean's drainage basins. Based on a box model we estimated the amount of unradiogenic Os and the Atlantic‐Mediterranean exchange rate to explain this offset. Os isotopic ratios of the pre‐evaporite sediments in the western Mediterranean are almost identical to that of the coeval ocean water. In contrast, equivalent sediments from the Florence Rise have significantly lower 187 Os/ 188 Os values. The offset in the Os isotopic ratio on the Florence Rise is attributed either to limited water exchange between eastern and western Mediterranean or to local effects associated with exhumation of the Troodos ophiolites (Cyprus). Key Points: Os isotope ratio of the Mediterranean Sea sediments registers the history of water exchange Unradiogenic Os isotope ratios of Messinian evaporite suggest limited inflow from the Atlantic The unradiogenic Os may be supplied from ultramafic rocks in the drainage basins